Factors Associated with Behaviors Toward End-of-life Care Among Chinese Oncology Nurses: A Cross-Sectional Study - Xiaoyu Wu; Zhihuan Zhou; Yiheng Zhang; Xiaoyan Lin; Meng Zhang; Fulin Pu; Meifen Zhang (Elsevier, 2021)
Summary: Purpose: The goal of this study was to describe the current status of oncology nurses' behaviors toward end of life (EOL) care in China and to explore the factors associated with oncology nurses' behaviors toward EOL care. Methods: A cross-sectional design was applied and a convenience sample of 1038 oncology nurses from 22 grade A hospitals were recruited into this study. A general social demographic data questionnaire was administered, and the Chinese version of Nurses' Behaviors of Caring for Dying Patients Scale was used to assess nurse behavior toward EOL care. The total score ranges from 40 to 200 points. Data were analyzed with SPSS 26.0 software. Results: Chinese oncology nurses' average score of holistic EOL care behaviors was 2.97 ± 0.59. Oncology nurses provide physical care most (3.81 ± 0.76), followed by family care (3.02 ± 0.86), and spiritual care (2.37 ± 0.67). Multiple regression analysis showed that a higher frequency of sharing EOL care experience with colleagues, in-service palliative care education, higher level of head nurse support for EOL patient care, more cases of EOL care, higher working position, and nurse's perceived high level of support were positively associated with behavior toward EOL care. These six factors explained 16.2% of the total variance. Conclusions: The results may help provide a basis for converting behavior for EOL care among oncology nurses and design interventions to better improve quality of life for EOL patients with cancer in China.